IsPETase Is a Novel Biocatalyst for Poly(ethylene terephthalate) (PET) Hydrolysis. (3rd March 2021) - Kan, Yeyi; He, Lihui; Luo, Yunzi; Bao, Rui
Abstract: Poly(ethylene terephthalate) (PET) is one of the most widely used synthetic polyesters, but also a major cause of plastic pollution. Because the chemical degradation of PET would be uneconomical and rather burdensome, considerable efforts have been devoted to exploring enzymatic processes for the disposal of PET waste. Many PET‐hydrolyzing enzymes have been reported in recent decades, some of which demonstrate excellent potential for industrial applications. This review sets out to summarize the state of investigation into Is PETase, a cutinase‐like enzyme from Ideonella sakaiensis possessing ability to degrade crystalline PET, and to gain further insight into the structure–function relationship of Is PETase. Benefiting from the continuing identification of novel cutinase‐like proteins and growing availability of the engineered Is PETase, we may anticipate future developments in this type of enzyme would generate suitable biocatalyst for industrial use. Abstract : Hitting the bottle : Is PETase is receiving increased attention for its ability to degrade crystalline PET, a major cause of plastic pollution. This review summarizes the current state of investigation into Is PETase and puts forward the necessity of utilizing and engineering Is PETase for industrial applications.